2017
DOI: 10.3233/cbm-170350
|View full text |Cite
|
Sign up to set email alerts
|

MiR-181a inhibits non-small cell lung cancer cell proliferation by targeting CDK1

Abstract: These data suggested that miR-181a plays a tumor suppressor and may be a potential therapeutic target for NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 18 publications
1
54
0
Order By: Relevance
“…Q. Shi et al (2017) found that MIR-181a inhibited proliferation of non-small-cell lung cancer cells by targeting CDK1.…”
Section: Discussionmentioning
confidence: 99%
“…Q. Shi et al (2017) found that MIR-181a inhibited proliferation of non-small-cell lung cancer cells by targeting CDK1.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐181a can function as a prognostic biomarke in acute myeloid leukemia (Guo et al, ). miR‐181a can inhibit NSCLC proliferation by inhibiting CDK1 (Shi et al, ). miR‐181a is able to inhibit macrophage activation in chronic liver injury (Li, Chang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the researchers observed that CDK1 and PIK3R1 genes shared the most abundant edges than the above genes in the sub-network, and were significantly up-regulated and down-regulated in NSCLC, separately. Currently, a few studies reported that the CDK1 gene were associated with carcinomas, including gastric, colorectal, breast, and lung cancers (36)(37)(38)(39). Moreover, published results showed that some non-coding RNA inhibited cell proliferation of NSCLC by targeting CDK1 (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a few studies reported that the CDK1 gene were associated with carcinomas, including gastric, colorectal, breast, and lung cancers (36)(37)(38)(39). Moreover, published results showed that some non-coding RNA inhibited cell proliferation of NSCLC by targeting CDK1 (39,40). Despite these results, the role of CDK1 in NSCLC is still vague.…”
Section: Discussionmentioning
confidence: 99%